A PCR/RFLP methodology to identify non-Amazonian Brazilian deer species - de Souza, Juliana Nogueira [UNESP]; de Oliveira, Márcio Leite [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Springer Nature, 2013)
Due to the necessity of using noninvasive samples to study animals as elusive as the deer that occur in Brazil, we realized it was important to develop a PCR/RFLP protocol to assist in identifying such samples. Thus we developed a protocol in which a fragment of the cytochrome b gene is digested with two enzymes: SspI, which distinguishes species of the genus Mazama from Blastocerus dichotomus and Ozotoceros bezoarticus, and TAQα1 which permits differentiation between the species B. dichotomus and O. bezoarticus. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Blastocerus; Cervidae; Mazama; Ozotoceros; Restriction enzymes